2017
DOI: 10.1007/s11284-017-1434-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern of soil nitrogen availability and its relationship to stand structure in a coniferous‐broadleaved mixed forest with a dense dwarf bamboo understory in northern Japan

Abstract: Natural disturbances create spatial patterns of the ecosystem processes and functions in natural forests. However, how dynamics and the spatial structure of forests relate to soil nitrogen dynamics is not well understood. We examined the spatial relationship between the distributions of canopy and understory species, and soil nitrogen dynamics in a natural coniferous‐broadleaved mixed forest with a dense understory of Sasa dwarf bamboo in northern Japan. The O horizon was thick where coniferous litter predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In forest ecosystems, understory vegetation can be an important factor impacting soil C and N processes [ 9 ] as has been documented by previous studies [ 10 , 11 ]. While understory vegetation represents only a small portion of forest biomass, it plays an important role in maintaining biodiversity, ecosystem stability, and sustainable productivity of forest ecosystems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In forest ecosystems, understory vegetation can be an important factor impacting soil C and N processes [ 9 ] as has been documented by previous studies [ 10 , 11 ]. While understory vegetation represents only a small portion of forest biomass, it plays an important role in maintaining biodiversity, ecosystem stability, and sustainable productivity of forest ecosystems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the dependence of soil C and N processes on understory vegetation types are not thoroughly understood [ 13 ]. Studies have shown that understory vegetation types impact soil temperature and moisture [ 14 ], microbial richness and composition [ 15 18 ], and C/N ratios [ 11 , 13 , 19 ]. For example, Wu et al [ 20 ] reported that removing understory vegetation from Eucalyptus forest decreased root biomass and soil organic matter input, and hence altered soil microbial community structure.…”
Section: Introductionmentioning
confidence: 99%
“…Forest vertical structure is shaped by species competition for light, water, and soil nutrients, as well as by forest succession and past disturbances [47]. Black locust canopy did not change significantly in the early stages of succession.…”
Section: Understory Stratification and Dynamicmentioning
confidence: 90%
“…The natural mixed broadleaf-conifer forest is widely distributed throughout Europe, North America, and the Far East. It is also one of the main forest types in northeast China and makes an important contribution to the national economy for its large percentage of wood consumed for civil and national purposes (Chen et al, 2017; Inoue et al, 2017; Knoke et al, 2008; Li et al, 2014; Namikawa, Okamoto & Sano, 2000). The composition and structure of the forest type vary among regions.…”
Section: Introductionmentioning
confidence: 99%